Moda sí, pero no así (2020)
This work has as its main theme fashion approached from a perspective that points towards sustainability through the application of the Upcycling technique. Through this, pieces are created with scraps of leather from the upholstery industry, which are inspired by the nineties to arrive at the final result of a jacket and a set (blazer and miniskirt) that materialize the pillars developed through research. The above being, conscious decision making, minimizing the impact generated on the environment and valuing human capital and the material worked.